The influence of early urodynamic test on outcomes of treatment of female urinary incontinence - Sosnowski, Marek; Łowicki, Roman (Menopause Review/Przegląd Menopauzalny, 2008)
Aim of the study: Establishing the preliminary diagnosis of urinary incontinence in the examined women and its comparison with the diagnosis after urodynamic investigations. Classification to an appropriate type of urinary incontinence (UI), qualification for appropriate treatment and assessment of its efficacy. Material and methods: A group of 159 women aged 25-85 years (mean age 59.2) who underwent urodynamic investigations because of UI between October 2004 and September 2006 was included in the study. The type of UI was provisionally diagnosed on the basis of anamnesis, micturition charts, Gaudenz, UDI-6 and IIQ-7 questionnaires, and gynaecological and urological examination. Then complex urodynamic tests were performed and the ultimate diagnosis of UI established. Therapeutic management of each patient, consistent with the recommendations of the Polish Society of Urology, was instituted according to the type and grade of UI. After 6 and 12 months since the institution of treatment, the patients again completed the UDI-6 and IIQ-7 questionnaires, as well as a questionnaire designed by us, assessing the effectiveness of the applied treatment method. Results: In the study group of 159 the following diagnoses were established: stress incontinence (SUI) in 112 (70.4%), mixed incontinence (MUI) in 25 (15.7%), urge incontinence (UUI) in 13 (8.2%), other incontinence types in 9 (5.7%). After exclusion of other incontinence types from the analysis on the basis of preliminary examinations, the distribution of diagnoses according to types was as follows: in 60% of cases SUI, in 34.7% MUI and in 5.3% UUI. After urodynamic tests the respective rates changed as follows: SUI – 74.7% of patients, MUI – 16.7% and UUI – 8.7%. During follow-up visits, cure and improvement were observed, on the basis of the completed questionnaires, in 56 (87.5%) patients after surgical treatment and in 44 (51.2%) after conservative treatment. According to UDI-6, improvement or marked improvement after treatment was reported by 49 (76.6%) patients after surgical treatment and only by 31 (36%) after conservative treatment. According to IIQ-7, improvement or marked improvement was obtained in 54 (84.4%) patients after surgical treatment and in 37 (36%) after conservative treatment. Conclusions: 1. Including urodynamic tests in the initial management protocol in patients with UI allows more precise diagnosis of incontinence type and results in increased rate of SUI diagnoses and a decrease of those of MUI. 2. The sensitivity and specificity of the applied questionnaires, Gaudenz and UDI-6, is the highest in diagnosis of stress incontinence. 3. The proposed treatment of UI in the study group was effective after 12 months in 87.5% of patients after surgical treatment and in 51.2% after conservative treatment.